Progress in Brown Teal Anas a. chlorotis conservation - Hayes, F Neil; Dumbell, Grant S (Wildfowl, 1989)
The Brown Teal population is now largely restricted to the Northland area of the New Zealand mainland, and to Great Barrier Island. Some success is being achieved in retarding the decline of teal on the mainland, and between 1984 and 1989 just over 500 captive-reared Brown Teal have been released in Northland. On Great Barrier Island, research has determined that the teal population is much higher than previous figures had indicated. This paper summarises progress in a unique conservation project that aims to halt the decline of an endemic bird and to ensure a future for the species. The project is Ducks Unlimited's 'Operation Pateke' which started in 1976.